THE PRICE OF PROGRESS: ECONOMIC GROWTH AND SOCIAL IMPACT (CAHIERS MAGELLANES-NS, 2024)
Economic growth is often seen as a positive force for societal improvement, bringing employment opportunities, technological advancements, and better living standards. However, the benefits of economic progress are accompanied by challenges such as increased inequality, urban migration, environmental degradation, and social disruptions. This paper examines the complex relationship between economic development and social impact, focusing on India’s experience since economic liberalization in 1991. Utilizing both quantitative data and qualitative interviews, the study explores how economic growth has influenced spatial inequality, income disparities, gender dynamics, and family structures. Key findings suggest that while GDP and mean income have significantly increased, so has income inequality, as evidenced by the rising Gini coefficient. Urbanization has progressed, yet this has led to a growing divide between urban and rural areas. Environmental indicators show worsening conditions, with increased CO2 emissions and declining air and water quality. Social impacts include shifts towards nuclear families, improved gender employment ratios, and enhanced social cohesion, although challenges remain. The paper underscores the importance of adopting inclusive policies that balance economic growth with social equity and environmental sustainability. It highlights the need for policy interventions that promote equitable distribution of wealth, improve rural incomes, and address environmental concerns. By integrating economic development with social and environmental goals, India can ensure that progress benefits all sections of society, fostering sustainable and inclusive growth.